2016
DOI: 10.1371/journal.pntd.0004269
|View full text |Cite
|
Sign up to set email alerts
|

Altered Hypercoagulability Factors in Patients with Chronic Chagas Disease: Potential Biomarkers of Therapeutic Response

Abstract: Thromboembolic events were described in patients with Chagas disease without cardiomyopathy. We aim to confirm if there is a hypercoagulable state in these patients and to determine if there is an early normalization of hemostasis factors after antiparasitic treatment. Ninety-nine individuals from Chagas disease-endemic areas were classified in two groups: G1, with T.cruzi infection (n = 56); G2, healthy individuals (n = 43). Twenty-four hemostasis factors were measured at baseline. G1 patients treated with be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 34 publications
(46 reference statements)
0
51
0
Order By: Relevance
“…This TPP should guide the development of tests to rapidly evaluate Chagas disease antiparasitic treatment efficacy. These tests might be based on biomarkers derived from the parasite, such as PFR2, KMP11, HSP70, the peptide 3973, F29, αGal-containing antigens, and the list of epitope-based antigens provided by Granjon and colleagues [28][29][30][31][32][33][34]; biomarkers derived from the host, such as hypercoagulability markers F1+2 and ETP [35], and the APOA1 and FN fragments [36]; or a combination of both. At present, preliminary results using Infinity antigen 3 (AG 3; derived from the parasite) and the SaMi-Trop cohort from Brazil show promise, but further insight is required to ensure that the 40% parasite clearance reported upon treatment persists over time [28].…”
Section: Discussionmentioning
confidence: 99%
“…This TPP should guide the development of tests to rapidly evaluate Chagas disease antiparasitic treatment efficacy. These tests might be based on biomarkers derived from the parasite, such as PFR2, KMP11, HSP70, the peptide 3973, F29, αGal-containing antigens, and the list of epitope-based antigens provided by Granjon and colleagues [28][29][30][31][32][33][34]; biomarkers derived from the host, such as hypercoagulability markers F1+2 and ETP [35], and the APOA1 and FN fragments [36]; or a combination of both. At present, preliminary results using Infinity antigen 3 (AG 3; derived from the parasite) and the SaMi-Trop cohort from Brazil show promise, but further insight is required to ensure that the 40% parasite clearance reported upon treatment persists over time [28].…”
Section: Discussionmentioning
confidence: 99%
“…F2/3 and A&T antigens obtained from parasites seem to be candidate surrogate biomarkers, but their use in adult studies needs to be further evaluated since the reduction in titers and seroreversion can take longer. Pinazo et al have shown that A&T CL-ELISA remains positive for 3 years after treatment in an adult population [36].…”
Section: Parasite Dna Amplification and Antigens For Serological Testsmentioning
confidence: 99%
“…These markers are elevated in the early stage of the chronic phase and decrease after therapy with BZN [52]. In a more recent study with 99 individuals, Pinazo et al observed that F 1 + 2 and ETP were abnormally expressed in 77% and 50% of infected patients before treatment but returned to, and remained at, normal levels 6-9 months after treatment in 76% and 96% of cases, respectively [36]. This data suggests these markers could assess short-term response to treatment; however, normal values can be observed in infected patients, and some patients show qPCR-positive results even when ETP values reach baseline after treatment.…”
Section: Host Prothrombotic and Immune Markersmentioning
confidence: 99%
“…Parasite persistence and unbalanced type 1 inflammatory immune response are likely the dominant determinants of Chagas’ cardiomyopathy. Autoantibodies and a hypercoagulability state might also be involved (13). …”
Section: Introductionmentioning
confidence: 99%